2015
DOI: 10.5751/es-07314-200145
|View full text |Cite
|
Sign up to set email alerts
|

Understanding adaptation and transformation through indigenous practice: the case of the Guna of Panama

Abstract: ABSTRACT. Resilience is emerging as a promising vehicle for improving management of social-ecological systems that can potentially lead to more sustainable arrangements between environmental and social spheres. Central to an understanding of how to support resilience is the need to understand social change and its links with adaptation and transformation. Our aim is to contribute to insights about and understanding of underlying social dynamics at play in social-ecological systems. We argue that longstanding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 65 publications
(73 reference statements)
0
33
0
1
Order By: Relevance
“…It was also a key epistemological driver of the emergence of the applied and transdisciplinary field of biocultural diversity (Maffi 2001). A recent example from applied resilience research showed that existing social and cultural practices of Guna indigenous peoples in Panama contribute directly to capacities for adaptation and transformation (Apgar et al 2015).…”
Section: Discussion: Toward a Resilient Research Culturementioning
confidence: 99%
“…It was also a key epistemological driver of the emergence of the applied and transdisciplinary field of biocultural diversity (Maffi 2001). A recent example from applied resilience research showed that existing social and cultural practices of Guna indigenous peoples in Panama contribute directly to capacities for adaptation and transformation (Apgar et al 2015).…”
Section: Discussion: Toward a Resilient Research Culturementioning
confidence: 99%
“…At the community scale, the wider psychology literature suggests that there is also a need to engage with overlooked questions of optimism, leadership, self-esteem and people's relationship to place in understanding agency and capacity for self-organisation in the face of emerging shocks and stressors Brown and Westaway, 2011;Miles, 2015;Apgar et al 2015). Second, assessments need to explore and exploit opportunities to build cross-scale relationships in support of learning and adaptation decision-making, rooted in and responding to an understanding of how pre-existing social and cultural relations influence access to and control over institutions (Cote and Nightingale, 2012;Dagdeviren et al 2015;Sjostedt, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has affirmed the role of individual well-being and identity in community resilience, recognising that well-being is underpinned by identification with a primary community, enhancing the ability of community members to cope (Miles, 2015). Shared cultural practices, such as those that support leadership, individual development and social networking, have been found to support resilience and transformation (Apgar et al 2015). Yet attributes such as neighbourliness can also emerge in response to shocks, even when good relations were previously absent (Cheshire, 2015).…”
Section: Adaptation and Resiliencementioning
confidence: 99%
“…The paper by Apgar et al (2015) on the Guna indigenous people illustrates the importance of considering cultural and spiritual dimensions of adaptation, transformation, and social-ecological resilience. They show how longstanding social and cultural processes have created enabling conditions that have fostered the Guna people's adaptive and transformational capacity.…”
Section: Paper Contributionsmentioning
confidence: 99%
“…The framework bridges social and ecological understandings of transformation and outlines the processes and phases of transformative change in an SES. It provides an avenue for analyzing the alteration of social-ecological feedbacks, critical barriers and leverage points, and outcomes of social-ecological transformations.The paper by Apgar et al (2015) on the Guna indigenous people illustrates the importance of considering cultural and spiritual dimensions of adaptation, transformation, and social-ecological resilience. They show how longstanding social and cultural processes have created enabling conditions that have fostered the Guna people's adaptive and transformational capacity.…”
mentioning
confidence: 99%